2021
DOI: 10.1007/s10899-021-10038-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Exposure to Different Gambling Advertising Types, Advertising Impact and Problem Gambling

Abstract: People with gambling problems report more exposure and impact from gambling advertising, although less is known regarding the role of specific advertising types. Data on gamblers (n = 5830, 48.5% women, mean age = 44.27) was collected from a general population cross-sectional survey in Norway (32.7% response rate). We examined if problem gambling was associated with perceived advertising impact (on gambling involvement, awareness, and knowledge) or exposure (via internet, TV, retail outlet, newspaper, and dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…In this study media advertising such as Dstv and Facebook/telegram were signi cantly associated with high-rate problematic gambling. This is in agreement with previous research ndings in Swedish (52), southern Australia (38), and Norway (53). This nding could be due to may normalize gambling among bettors, grooming a new generation of gamblers, promoting gambling as healthy harmless fun that, like sport, relies on skill, and contributing to the increase in problem gambling related to sports betting (30).…”
Section: Discussionsupporting
confidence: 93%
“…In this study media advertising such as Dstv and Facebook/telegram were signi cantly associated with high-rate problematic gambling. This is in agreement with previous research ndings in Swedish (52), southern Australia (38), and Norway (53). This nding could be due to may normalize gambling among bettors, grooming a new generation of gamblers, promoting gambling as healthy harmless fun that, like sport, relies on skill, and contributing to the increase in problem gambling related to sports betting (30).…”
Section: Discussionsupporting
confidence: 93%
“…Gambling is no different, and multiple studies have reported positive associations between advertising and marketing across different media, and gambling behaviour, attitudes or intentions (Bouguettaya et al, 2020). Exposure to gambling marketing is thought to be particularly harmful for specific groups including children and young people (Clemens et al, 2017;Hing et al, 2014;Pitt et al, 2016), and those experiencing gambling harms (Hanss et al, 2015;Syvertsen et al, 2021). The current results demonstrate consistent exposure through the matchday programme, often through multiple instances of brand exposure on the same page.…”
Section: Discussionsupporting
confidence: 57%
“…Higher advertising volumes are to be expected with the admission of new forms of gambling into the German market by the new State Treaty of Gambling. Since exposure to gambling advertising might be positively associated with problem gambling (Syvertsen et al, 2021 ), an increase in the latter might be expected. This will fuel the demand for the regulation of gambling advertising that, thus far, has not been considered by regulators.…”
Section: Discussionmentioning
confidence: 99%